PENGEMBANGAN INSTRUMEN TES PENGUASAAN KONSEP REPRESENTASI KIMIA PADA LIMA INDIKATOR ASAM BASA DARI ALAM : ANALISIS DENGAN RASCH MODEL - Khoerul Ummah; Julia Mardhiya; Sri Mulyanti (UIN Sumatera Utara Medan, 2022)
This study developed a test instrument for mastering the concept of chemical representation on five natural acid-base indicators. This test aims to determine the mastery of macroscopic, submicroscopic and symbolic chemical concepts. Product trial data processed using the Rasch model assisted by Winstep software. The result showed that the instrument was valid as evidenced by a unidimensional test, person reliability was in good category, item reliability was in sufficient category, Cronbach alpha was in very good category. questions, the value of separation person is divided into three groups, the developed test instrument meets the criteria for the level of difficulty index according to the Rasch Model item response. All items are stated to have good accuracy and can measure students' abilities well.